PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KEJELASAN SASARAN ANGGARAN, PROFESIONALISME SUMBER DAYA MANUSIA DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL (STUDI KASUS PADA SKPD KABUPATEN PESAWARAN) - Ferin Annisa; Eka Sariningsih; Muhammad Luthfi (Jurnal Ilmiah Akuntansi Rahmaniyah, 2020)
Managerial Performance, namely the work units of public organizations are expected to create a conducive work environment by integrating the leadership capabilities and abilities of subordinates. The purpose of this study was to determine how much influence budgeting participation, clarity of budget targets, professionalism of human resources, organizational commitment and work motivation on managerial performance. Data was collected by Purposive Sampling, with a sample of 96 respondents involved in budgeting. The analysis technique used is the Partial Least Square (PLS) model. The test results show that the partial hypothesis of budgeting participation, professionalism of human resources, organizational commitment and work motivation have an influence on managerial performance. While the clarity of the budget target does not affect managerial performance. The result of the determination coefficient test (R2) is around 0.611.